2020
DOI: 10.1155/2020/2064781
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Extracorporeal Shock Wave Therapy for Lateral Epicondylitis: A Systematic Review and Meta-Analysis

Abstract: Background. Lateral epicondylitis (LE) is a common elbow problem. Extracorporeal shock wave therapy (ESWT) was widely used in the treatment of LE and has been shown to relieve the pain and functional impairment (loss of grip strength) caused by tennis elbow. However, the evidence with regard to whether ESWT has better clinical efficacy over other method is not clear. The aim of the study was to compare the effectiveness of ESWT with other techniques in the treatment of LE. Methods. Literature searches of PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 39 publications
0
31
1
4
Order By: Relevance
“…Although a clinical superiority of the method was suggested, these recommendations should be treated with caution as minimal clinically important differences were not used for the interpretation of their study results. 12,13 There was an overestimation of the effectiveness of shockwave therapy compared to our findings which can be explained due to several methodological differences. Firstly, a substantial clinical heterogeneity of the types of interventions including sham treatment, wrist splint, laser, multimodal physiotherapy and corticosteroid injections was found in their quantitative synthesis.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…Although a clinical superiority of the method was suggested, these recommendations should be treated with caution as minimal clinically important differences were not used for the interpretation of their study results. 12,13 There was an overestimation of the effectiveness of shockwave therapy compared to our findings which can be explained due to several methodological differences. Firstly, a substantial clinical heterogeneity of the types of interventions including sham treatment, wrist splint, laser, multimodal physiotherapy and corticosteroid injections was found in their quantitative synthesis.…”
Section: Discussioncontrasting
confidence: 93%
“…Previous meta-analyses 12,13 reported significantly better results for extracorporeal shockwave therapy compared with other treatments in pain reduction and grip strength. Although a clinical superiority of the method was suggested, these recommendations should be treated with caution as minimal clinically important differences were not used for the interpretation of their study results.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Despite methodological heterogeneity, the authors concluded there was effectiveness of ESWT for lateral elbow tendinopathy when well-defined restrictive study parameters are appropriately implemented. A recent systematic review and metaanalysis included 13 studies and 1035 patients comparing ESWT with other treatments for lateral elbow tendinopathy [113]. Meta-analysis showed that ESWT was superior for pain and function (loss of grip strength) compared to other treatment methods.…”
Section: Lateral Elbow Tendinopathymentioning
confidence: 99%